Preoperative imaging and surgical repair of a coronary sinus septal defect: A case report. (June 2022) - Krivenko, Gabriel; Maag, Brenden; Nelson, Jennifer S.; Madueme, Peace; Douglas, Kathryn; Dorotan-Guevara, Maria Malaya
Abstract: Background: Coronary sinus septal defect is a rare congenital anomaly in which there is an aberrant communication between the left atrium and coronary sinus. Diagnosis may be challenging; however, a multi-modal approach can aid in diagnosis and lead to timely repair. Aim of review: This case describes a 6-month-old female with unexplained right heart enlargement who was diagnosed with coronary sinus septal defect by utilizing transthoracic echocardiogram and cardiac magnetic resonance imaging. The use of multiple imaging modalities was crucial in preoperative planning and successful repair. Key scientific concepts: Early identification of coronary sinus septal defects is key in reducing long term cardiovascular disease. Although echocardiogram is adequate to identify a coronary sinus septal defect, cardiac magnetic resonance imaging is beneficial for preoperative evaluation. A multi-modal strategy is crucial in ensuring optimal outcomes for patients with rare cardiac malformations. Highlights: Coronary sinus septal defect can be a singular defect or may be associated with other cardiac anomalies. Cardiac magnetic resonance imaging is beneficial in preoperative evaluation. Echocardiography alone may miss difficult-to-image cardiac anomalies. Multi-modal strategies are crucial in identifying and treating rare cardiac defects.